Improved electrochemical performance of pyrolytic graphite paper: Electrochemical versus reactive cold-plasma activation - Jian F.S. Pereira; Pedro H.S. Borges; Gabriel M. Moura; Rogério V. Gelamo; Edson Nossol; Sheila C. Canobre; Eduardo M. Richter; Rodrigo A.A. Munoz (Electrochemistry Communications, 2019)
Flexible pyrolytic graphite sheets or graphite paper (GP) are a promising source of disposable (low-cost) electrochemical sensors. This work demonstrates the improvement in the electrochemical performance of graphite paper either after a simple electrochemical activation in acid media using cyclic voltammetry or after cold reactive plasma treatment using CO2 and O2 gases. Cyclic voltammetry of the redox probe ferri-ferrocyanide showed higher electrochemical reversibility on the treated surfaces, which was corroborated by the electrochemical impedance spectroscopy (lower charge transfer resistance). Scanning electron microscopy revealed a high number of grooves on the treated surfaces after both electrochemical and plasma treatments and Raman spectroscopy showed more structural defects (higher D/G ratios), which may explain the improved cyclic voltammetric response of the redox probe. As a proof-of-concept, the graphite paper was evaluated for dopamine detection using cyclic voltammetry and amperometry under flow conditions. Improved performance on treated surfaces, especially after CO2-plasma treatment, was verified. The electrochemical activation is a simple strategy to improve the sensing properties of graphite paper; however, cold-plasma treated surfaces provided better sensing properties probably due to the production of higher number of structural defects. Keywords: Carbon-based electrodes, Disposable electrochemical sensors, Graphite foil, Paper electrodes, Batch-injection analysis